Impact of Intestinal Helminth Infections on Malnutrition and Haematological Indices of School-Age Children in Gondar Town, Ethiopia - Tarekegn, Daniel; Birhanie, Meseret; Lemma, Wossenseged (International Journal of Nutrition, 2022)
In Ethiopia stunting, underweight and wasting in school children are very common. The aim of this research was to evaluate the impact of intestinal helminthes and schistosomiasis on malnutrition, anaemia and haematological indices in the school age children of Azezo Elementary School in Gondar town. Kato Katz technique was performed to determine infection and intensity of intestinal helminth infections. AnthroPlus software version 1.04 was used to get malnutrition indices while fully automated haematological analyzers were used to determine haematological and biochemical parameters. A total of 384 school children were recruited in this study. The overall prevalence of helminth infection was 45.8% (178/384) with the leading Ascarislumbericoides infection (20.6%) compared to the second leading Schistosomamansoni (17.4%) and third leading hook worm infections (13.3%). The prevalences of body mass indexes for age Z-scores (BAZ) indices were 9.6% (37) very sever thin, 17.2% (66) sever thin, 38.3% (147) thin, 34.4% (132) normal and 0.5% (2) overweight. On the other hand, the prevalences of height for age Z-scores (HAZ) indices were 12.2% (47) stunt, 87% (334) normal and 0.8% (3) over height. Of the total 384 school age children, 335 (87.2%) had normal blood glucose level (70 – 110 mg/dL) while the remaining 49 (12.8%) school age children were hypoglycemic. The number of the school children with normal total protein level (6.6 – 8 g/dL) was 259 (67.4%) while the remaining 125 (32.6%) school children were hypo-proteinaemic. The prevalence of anemia in the school age children was 33.1% (127). Intestinal helminth infections were statistically significantly associated (p = 0.000) with hypo-proteinaemia, anemia and number of lymphocytes compared with non-infected school children. The likelihood of anemia in intestinal helminth infected school children, when it was compared with uninfected, was 148 times higher for both Ascaris lumbericoides-Schistosoma mansoni co-infection, 38 times for Hookworm, 20 times for Schistosoma mansoni and 3 times for Ascaris lumbericoides mono-infections. Conclusion: Intestinal helminth infections in school age children aggravate malnutrition. Prolonged malnutrition and intestinal helminth infections could result in stunting in school-age children.
Keywords: School children; malnutrition; intestinal helminth infections; nutritional indices; Gondar town.